Photo-induced coupling reactions of tetrazoles with carboxylic acids in aqueous solution: application in protein labelling. Issue 25 (8th March 2016) - Zhao, Shan; Dai, Jianye; Hu, Mo; Liu, Chang; Meng, Rong; Liu, Xiaoyun; Wang, Chu; Luo, Tuoping
Abstract : The coupling reactions of diaryltetrazoles with carboxylic acids under UV irradiation were investigated. Application of these transformations in chemical biology was demonstrated in photo-labelling the proteinogenic carboxylic acids in purified proteins, cell lysates and living cells. Abstract : The photo-induced reactions of diaryltetrazoles with carboxylic acids in aqueous solution were investigated. Besides measuring the apparent second-order rate constant and evaluating the functional group compatibility of these reactions, we further incorporated the tetrazoles into SAHA, leading to a new active-site-directed probe for labelling HDACs in both cell lysates and living cells.